Materiality: global history and the material world - Gänger, Stefanie (Rethinking global history, 2024)
This chapter studies global histories that consider aspects of the material world. It exposes the – often tacit – assumptions that guide these global material histories and holds them up for careful inspection. Its particular interest is in the grounds on which global material historians associate matter and material culture with a specific scale, context or level of observation: with world-making, the global scale and ‘connectivity’, but also with the concrete, the ‘micro’ and the intimate. In that context, the chapter discusses a wide range of themes, from the risk of fetishising material things – as in, reverencing them for properties, including ‘global’ ones, merely projected onto them – to the inevitability of canvassing some forms of materiality on a global scale: the pollution of air, for instance, or, for the post–Cold War era, the issue of resource shortages. The chapter argues that, like any form of historical writing, global material histories are under the influence of their practitioners’ own times’ socioreligious texture, global imaginary and discursive habits; mindful of the telos and conceptions that pervade their work, they will be better prepared to see the world of matter and material culture in all its changeability, elusiveness and polysemy.